Pembuatan video tutorial pengetahuan produk aplikasi SilviPlus dengan teknik motion graphic di PT KST - Kaisar Renaisance Al-Ars; Nabila Fakhiratunisa; Merry Ardelia Wirastuti; Mochamad Farras Fauzan; Joddy Lintar Balle; Muhammad Shubhi Maulana; Mira Fitria Dewi; Tria Febriayanti; Vandame Ronald Suhada; Naufal Alif Falah; Sabila Rodhia; Teuku Rizha; Ridwan Siskandar (PUSAT SAINS INDONESIA, 2021)
Innovation and technology have brought benefits in everyday life that have an impact on all aspects of people's lives, including how to obtain and convey information. Multimedia is one of the media for delivering information that is often used today. This time the author focuses on the SilviPlus application which is a Point of Sale application designed according to the needs of MSMEs. T he SilviPlus application strongly supports MSME business players in Indonesia to carry out digital transformation in terms of sales and bookkeeping transactions, so that changes will be faster from cash transactions to cashless transactions. This study aims to provide education about the SilviPlus application to business users so that they can understand the use of the application easily. The results of this study are 6 video motion graphic products made with Adobe Illustrator, Adobe After Effects. After testing the product, it was found that 77% stated